Investigating transmembrane TNF and transmembrane p55TNFR mediated signaling in host immune function during Mycobacterium tuberculosis infection - Dambuza, Ivy M (Department of Clinical Laboratory Sciences, 2014)
The importance of TNF-TNFR signaling in immunity against M. tuberculosis has been established. The aims of this study were to characterize the functions of membrane-bound TNF (Tm-TNF) and soluble TNF (solTNF) and to investigate the role of membrane-bound p55TNFR signaling as well as the in vivo significance of TNFR shedding in host immune responses during infection with M. tuberculosis H37Rv. To address this, mice expressing only the membrane-bound TNF or membrane-bound p55TNFR were exposed to a low dose of M. tuberculosis H37Rv by aerosol inhalation infection. The results presented in this dissertation illustrate that Tm-TNF mice were able to control acute M. tuberculosis infection but succumbed to chronic exposure to M. tuberculosis with pneumonia. We demonstrate that Tm-TNF mice displayed heightened pulmonary macrophage activation reflected by enhanced cell surface expression of MHC-II, CD80 and CD86 as well as enlargement of granulomas. Furthermore, our results show that solTNF has a regulatory function that modulates the magnitude of Th1 immune responses during acute and chronic stages of the infection. The evaluation of the functions of Tm-TNF and solTNF in host immune function in the presence of an established mycobacteria-specific immune response was carried out using a 'drug-based' M. tuberculosis reactivation model. Here, mice that were challenged with a low dose of M. tuberculosis were exposed to INH-RIF treatment for six weeks in drinking water, after which therapy was withdrawn and immune responses during reactivation were analyzed. Our results demonstrate that complete absence of TNF resulted in host susceptibility to recrudescence tuberculosis in the presence of a mycobacteria-specific immune response. TNF deficient mice were unable to suppress bacilli growth and formed diffused granulomas and succumbed early to reappearing tuberculosis compared to WT mice. By contrast, we show that Tm-TNF was sufficient for containment of reappearing mycobacterial growth and sustaining immune pressure in a manner comparable to WT control mice. xii Lastly, the analysis of host immune responses in mice expressing a non-sheddable p55TNFR revealed that persistent p55TNFR cell surface expression does not afford better protection to low dose M. tuberculosis infection. However, we observed a transient elevation in the frequency of pulmonary CD11b+/MHC-II+ cells in mice expressing a non-sheddable p55TNFR relative to WT mice as well as reduced cell surface expression of CD44 on CD4+ T cells. We also found that pulmonary IL-12p70 and TNF concentrations were elevated whereas IFNÎ³ levels were reduced in mice expressing a non-sheddable p55TNFR relative to WT mice. Furthermore, data presented here describe the in vivo functional significance of p75TNFR shedding. We demonstrate using a double mutant mouse strain that in the absence of p75TNFR, mice expressing a non-sheddable p55TNFR display enhanced ability to control M. tuberculosis infection.